التنمية السياسية في ليبيا "المعوقات والفرص" (Comprehensive Journal of Science, 2026)
Most developed and developing countries alike recognize the great importance of political development, striving to achieve or maintain it due to its significant role in achieving political, social, and economic stability. However, most developing countries, especially newly independent ones, have faced considerable obstacles in keeping pace with political development, as they suffer from numerous impediments. This study examines the Libyan case, which suffers from a confluence of political development crises. The study focuses on the most significant obstacles to political development in Libya, while also highlighting the most important available opportunities that can be utilized to achieve genuine political development.
Keywords: Political development - Political modernization - Democratic transition - Crises of political development